Effect of core training on skill-related physical fitness performance among soccer players: A systematic review - Luo, Shengyao; Soh, Kim Geok; Zhang, Lingling; Zhai, Xiuwen; Sunardi, Jaka; Gao, Yongqi; Sun, He (Frontiers in Public Health, 2023)
This study aims to present an in-depth review of the available literature on the effect of core training on skill-related physical fitness performance among soccer players, as well as to offer suggestions for further research for researchers and coaches. Methods: The data in this study were presented based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. Using scientific databases and web search engines including Scopus, Ebscohost, Web of Science, PubMed, and Google Scholar, researchers collected studies from the published literature. Only 26 of the 75 articles satisfied all the inclusion criteria and were thus included in the systematic review. The quality of each study was determined using the PEDro scale. The scores for 26 studies range between 4 and 6. Result: Core training can improve soccer players' skill-related physical fitness, including their power, speed, balance, and agility. Conclusion: The core is the anatomic and functional center of the body, as well as its ‘engine’. All movements emanate from the center of the body and are transmitted to the extremities. The core muscles differ from the limb muscles because they frequently cocontract, thus making the torso hard to the point whereby all the muscles work together to become synergists. Theoretically, a strong core permits the passage of force from the lower body to the upper body with minimal energy loss in the torso. Based on the 26 studies, this review suggests that core training should be incorporated into the daily training sessions of soccer players, with a minimum frequency and length of 15 minutes per training session, twice per week, for four weeks.